An Appraisal of the Legal Framework on Parole in Nigeria - Ayinde, Dare Joseph (Potchefstroom Electronic Law Journal, 2022)
Parole is a new correctional measure in the Nigerian penal system. Before 2015 inmates could be released before the expiration of their terms of imprisonment only if they were granted pardons by the governor of a state or by the president. However, this has changed with the coming into force of the Administration of Criminal Justice Act of 2015 (ACJA). The ACJA empowers courts, upon the recommendation of the comptroller-general of the Nigerian Correctional Service, to release inmates on parole. The ACJA also states the two conditions that the comptroller-general must consider before he recommends inmates for parole. The first condition is that the inmates must be of good behaviour, and the second is that the inmates must have served their non-parole periods. While there is no ambiguity on the first condition, the scope of the second condition is not well stated in the ACJA. The ACJA states that inmates that are sentenced to at least fifteen years or life imprisonment must have served at least one-third of their sentence before they can be recommended for parole. However, the ACJA does not state the minimum period that inmates who are sentenced to less than fifteen years of imprisonment must have served before they can be recommended for parole by the comptroller-general. Second, life imprisonment in Nigeria theoretically means imprisonment for the remaining period of the natural life of the inmates upon whom such a sentence has been imposed. In this light it is not clear how the comptroller-general would calculate one-third of an indeterminate sentence for the purpose of determining when to recommend such inmates for parole. Another notable omission in the ACJA is that it does not state the conditions that courts may attach to the release of inmates on parole. Also, ACJA does not make provision for medical parole. To make parole an effective correctional measure in Nigeria, this article suggests that the ACJA should be amended to address all these weaknesses.